Using strategy mapping and cause-and-effect relationship for measuring ITSP implementation. - Jusoh, Yusmadi Yah; Hamdan, Abdul Razak; Aziz, Deraman (IJCSNS (International Journal of Computer Science and Network Security), 2009)
The Information Technology Strategic Planning (ITSP) was developed to lead and reflect the organizational achievement and future aspiration. The plan basically includes the information technology (IT) goals and strategies for the next few years. The intention was to justify IT contributions towards the efficiency, effectiveness and competitiveness. The plan may comprise of associated IT projects to achieve the planning strategies. Previous study has concluded that most of the plans are usually hard to manage due to various projects involved. Therefore, many performance measurement models and frameworks have been investigated and exploited to address the problem. Measuring ITSP implementation is important to justify the achievement of the planned projects. The focus of this paper is describing the application of the strategy mapping and cause and- effect relationship approach on measuring the achievement of the strategies and projects involved in the ITSP. This paper also report on the testing results of the related approach on the real case study to identify its applicability and measurability.